Formation of anthroponomical system of the modern Kazakh language in higher school - Suleimenova, Gulmira; Karlygash Sarbasova, Gulnara Syrlybayeva, Kuldirsin Saryhova, Raushan Assylova (Opción, 2020)
The purpose of the article is to select and systematize the topical problems of anthroponymy for educational purposes in order to form a holistic understanding of the anthroponymic system of the Kazakh language and skills. The methods of comparative analysis, system, and logical analysis, method of information generalization were used in conducting the research. As a result, the structural-word-forming type of personal names is the Turkic model. In conclusion, for today, the need for the special study of the proper names is the universally recognized fact, and ignoring them at learning any language makes the training process incomplete.